A Digital Partograph Model As Learning Media For The Normal Childbirth Care - Amelia, Kiki (International Journal of Psychosocial Rehabilitation, 2020)
This research is aimed to design the digital partograph application as learning media for the normal childbirth care and to know the level of model suitableness of the digital partograph as learning media for the normal childbirth care. The type of this research is Reseach and Development (R&D) method. This method needs several procedures started from need analysis, model design, model development, formative assessment, and the final product. The subject of this research is the midwifery students in second level of STIKES Nani Hasanuddin Makassar. The technique for collecting data is conducted by questionnaire. The data analysis applies a quantitative data analysis. The result shows that the digital partograpgh model as learning media for the normal childbirth care assessed by the material expert gets the average score about 3.8 (very good), assessment of media expert about 3.4 (good), and the assessment of students gets the average score about 4.3 (very good). Thus, it can be assumed that the digital partograph model as learning media for the normal childbirth care is suitable to be used to learning media.